2003
DOI: 10.1126/science.1084550
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Bacterial Biofilm-Like Pods in Urinary Tract Infections

Abstract: Escherichia coli entry into the bladder is met with potent innate defenses, including neutrophil influx and epithelial exfoliation. Bacterial subversion of innate responses involves invasion into bladder superficial cells. We discovered that the intracellular bacteria matured into biofilms, creating pod-like bulges on the bladder surface. Pods contained bacteria encased in a polysaccharide-rich matrix surrounded by a protective shell of uroplakin. Within the biofilm, bacterial structures interacted extensively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
879
0
16

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 1,016 publications
(916 citation statements)
references
References 29 publications
21
879
0
16
Order By: Relevance
“…UPEC have been shown to form biofilm-like structures (pods) in the urinary tract (30,31). By contrast, we made the observation that capsule-producing strains have a very limited ability to form biofilm in our microfermentor model.…”
Section: Discussionmentioning
confidence: 95%
“…UPEC have been shown to form biofilm-like structures (pods) in the urinary tract (30,31). By contrast, we made the observation that capsule-producing strains have a very limited ability to form biofilm in our microfermentor model.…”
Section: Discussionmentioning
confidence: 95%
“…P pili contain an adhesin, PapG, that recognizes a globoside receptor in the human kidney as part of a mechanism important in the disease process (3,4). Type 1 pili contain the FimH adhesin that mediates E. coli binding, invasion, and formation of intracellular biofilm-like bacterial communities in the bladder epithelium (5,6).…”
mentioning
confidence: 99%
“…It appears from light microscopy and EM data that the IBC closely associates with keratin intermediate filaments. 59,61 It was suggested that the intermediate filaments may provide scaffolds for the development of intracellular biofilms of UPEC. 61 The bacteria we visualized may reflect the early stage of the IBC development.…”
Section: Intermediate Filament Bundles Of the Umbrella Cells Provide mentioning
confidence: 99%